Dietary levels of Mannanoligosaccharide (MOS) for nile-tilapia (Oreochromis niloticus): Intestinal Morphology - Flavio Endrigo Cechim; Arcangelo Augusto Signor; Vinicius Pimenta Cividanes; Francielli Baioco Sales; Tiago Ferreira da Silva; Regianne Michele Dias Viana; Ricardo Yuji Sado (Boletim de Indústria Animal, 2012)
Intensification of aquaculture production systems exposes fish to numerous stressors, which may negatively affect their growth and limit profitability of aquaculture systems. In addition, fish farmers are now obliged to conform to Best Management Practices (BPMs) regulations. This current setup favors the use of dietary prebiotics for management of farmed fish as environmentally friendly practice. Mannanoligosaccharides (MOS) are complex carbohydrates derived from yeast (Saccharomyces cerevisiae) cell walls. This study was set out to evaluate the effects of increasing levels of dietary MOS on intestinal morphology of Nile-tilapia. Fish (12.62 ± 0.38 ) were randomly distributed into 16 cages (0.25m3 polyvinyl chloride; 20 fish per cage), inside four 5m3 net-cage at Salto Caxias Hydroeletric water reservoir (Boa Vista da Aparecida, PR) and fed diets containing increasing levels of MOS (0.0; 0.2; 0.4 and 0.8%) during 30 days (n=4). The proximal intestine fragment of two specimens from each replicate was taken for histological observations. The histological sections (5 μm) were stained with haematoxylin and eosin (H & E) and documented photographically with a digital camera (DCM 130E digital camera for microscope 1.3 pixels, CMOS chip Software Scopephoto) connected to a light microscope (EDUTEC 502 AC). The images were analyzed by using (BEL Eurisko) software for intestinal villi measures. Water quality parameters (temperature, pH and dissolved oxygen) were monitored during trial. It was observed influence (p<0.05) of MOS supplementation on Nile tilapia intestinal morphology. Fish fed diet containing 0.4% MOS supplementation showed increased (p<0.05) villi height (436.98±66.81 μm) when compared to fish fed unsupplemented control diet (401.01±70.73 μm), 0.2% (364.59±61.68 μm) and 0.8% (404.08±61.62 μm). Mannanoligosaccharides (MOS) are complex carbohydrates derived from yeast (Saccharomyces cerevisiae) cell walls and present mannose as primary carbohydrate, providing substrate for selective attachment of pathogenic intestinal bacteria, impairing bacterial adhesion to entherocytes, thus preventing infection of host cells. Thereby, the inhibition of bacteria adhesion to enterocytes prevents formation of mixed colonies, the entrapment of nutrients for bacterial growth and infection of host cells, leading to better gut health by increasing regularity, height and integrity of the gut villi and consequent better utilization and absorption of nutrients. In conclusion, dietary MOS at 0.4% supplementation for 30 days presented prebiotic effects for juvenile Nile-tilapia.